2014
DOI: 10.1007/s40617-014-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Social Validity Assessment of Training Methods to Improve Treatment Integrity of Special Education Service Providers

Abstract: We report the results of a social validity assessment that was administered to special education service providers (N=44) to document the acceptability and effectiveness ratings of several treatment integrity training methods. The participants judged performance feedback as the most likely method to improve their treatment integrity, followed by avoidance (negative reinforcement) of supervision meetings, online training, and financial incentive. Performance feedback was also rank-ordered as most effective amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
2
27
0
2
Order By: Relevance
“…In addition to the demonstrated effectiveness of BST, the treatment package also has a high acceptability rating among participants (e.g., Gunby & Rapp, ; Hassan et al, ; Hassan et al, ). The perceived acceptability of a treatment is critical, as it may help to better inform program selection (Baer & Schwartz, ) and has been shown to impact treatment adherence (Strohmeir, Mule, & Luiselli, ). The utility and widespread application of BST provides support for evaluating the applicability of teaching volunteers how to support individuals with DD in a physical education program.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the demonstrated effectiveness of BST, the treatment package also has a high acceptability rating among participants (e.g., Gunby & Rapp, ; Hassan et al, ; Hassan et al, ). The perceived acceptability of a treatment is critical, as it may help to better inform program selection (Baer & Schwartz, ) and has been shown to impact treatment adherence (Strohmeir, Mule, & Luiselli, ). The utility and widespread application of BST provides support for evaluating the applicability of teaching volunteers how to support individuals with DD in a physical education program.…”
Section: Introductionmentioning
confidence: 99%
“…Some of this research is currently underway. For example, recently Strohmeier, Mulé , and Luiselli (2014) assessed the social validity of training methods and found that special education service providers judged performance feedback as the most likely, and the most effective, method to improve their treatment integrity. Additionally, researchers have provided some guidelines for effective training (Behavioral Skills Training, BST;Parsons, Rollyson, & Reid, 2013) as well as how to assess and improve staff performance (Carr, Wilder, Majdalany, Mathisen, & Strain, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The percent of indicators rated a 4 or 5 on the 5-point scale on the field test surveys were computed for ascertaining if the social validity ratings reached a generally agreed upon level (85%) of acceptability and importance (e.g., Carter, 2009;Finn & Sladeczek, 2001;Meadan, Ostrosky, Zaghlawan, & Yu, 2009;Strohmeier, Mulé , & Luiselli, 2014). The percent of indicators rated as acceptable and important were computed separately for the performance checklists, practice guides, and the compatibility of the checklists and practice guides.…”
Section: Methods Of Analysismentioning
confidence: 99%